Measurement and control system of dissolved oxygen concentration for aerobic fermentations - Alvarez Icaza, Manuel; Macías López, Alfonso (Revista Mexicana de Ingenieria Biomedica, 2018)
The main features and design considerations of a system for the measurement and control of disolved oxygen concentration, in aerobic fermentation processes, are described. The system's prototype was designed and constructed entirely at the Centro de Instrumentos, UNAM. It allows for a +-2% regulation of the disolved oxygen contents. A main feature of the system is the simplicity of the oxygen sensing electrode.